Structural basis for ligand recognition of the neuropeptide Y Y2 receptor - Tingting Tang; Christin Hartig; Qiuru Chen; Wenli Zhao; Anette Kaiser; Xuefeng Zhang; Hui Zhang; Honge Qu; Cuiying Yi; Limin Ma; Shuo Han; Qiang Zhao; et al. (Nature Communications, 2021)
The human neuropeptide Y receptor Y2 (Y2R) is a drug target for the treatment of obesity and anxiety. Crystal structure of Y2R bound to a selective antagonist and accompanying mutagenesis provide insights into ligand recognition and subtype specificity of NPY receptors.